Estrategias de afrontamiento y autoestima en docentes de la Unidad Educativa Cristiana Nazareno. Riobamba, 2019 - Darío José, Hernández Vargas (2020)
The present research work was carried out in the “Christian Educational Nazarene Unit”, the objective of this study was to analyze the coping strategies and self-esteem present in the teachers who work in the institution. The population and sample consisted of 30 teachers between men and women. The type of research was quantitative; the revised WOC-R Coping Modes Scale was used to learn about coping strategies and the Rosenberg Self-Esteem Scale to assess self-esteem levels. Among the most outstanding results of the statistical analysis, it was determined that 70% of teachers use positive reevaluation, and 10% use self-control, these being the coping strategies mostly used by teachers. Regarding the scale used to evaluate the levels of self-esteem, it was found that 93% of the teachers maintained high self-esteem, 6% had medium self-esteem, and no teacher showed low self-esteem. Based on the results obtained, a psychological intervention plan was designed to help boost self-esteem and strengthen coping strategies for teachers from the Christian Nazarene Educational Unit.